2022
DOI: 10.1111/nhs.12982
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses' experiences of caring for patients in hospitals transitioning from curative to palliative care: A qualitative study

Abstract: The aim of this study was twofold: to illuminate registered nurses' experiences of palliative care and of caring for patients transitioning from curative to palliative care in hospitals. A qualitative descriptive design was used. Group interviews were conducted with 11 registered nurses in three different hospital settings. Content analysis was performed. The results are presented in four themes: "Understanding palliative care in a hospital setting"; "Involving, supporting, and caring for patients and families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…This concurs with a study done in Sweden that showed registered nurses struggled with understanding of palliative care and transfer of knowledge into clinical practice [19].As noted in another study Nursing students need to comprehend how to handle a patient's death, providing compassionate support to the patient's family, friends, and loved ones as they grapple with death and psychological trauma [11] since they tend to spend more time at the bedside with patients than other healthcare professionals.…”
Section: Discussionsupporting
confidence: 84%
“…This concurs with a study done in Sweden that showed registered nurses struggled with understanding of palliative care and transfer of knowledge into clinical practice [19].As noted in another study Nursing students need to comprehend how to handle a patient's death, providing compassionate support to the patient's family, friends, and loved ones as they grapple with death and psychological trauma [11] since they tend to spend more time at the bedside with patients than other healthcare professionals.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, death is a classic example of medicalization (Illich, 1976), which is a process by which social and personal issues are understood as medical problems requiring clinical management (Zola, 2005). Medicalization should not be understood as an imposition of medical power (Conrad, 1992), because as many palliative care physicians will report, family members are often the ones who have a very difficult time accepting death and push for continued treatment (Lind, Bengtsson, Alvariza, & Klarare, 2022). Medicalization is perhaps better understood as a form of "collusion" between us and our fears of death and medicine's utopian aspirations.…”
Section: The Medicalization Of Deathmentioning
confidence: 99%